2020
DOI: 10.1101/2020.09.23.309765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PspA adopts an ESCRT-III-like fold and remodels bacterial membranes

Abstract: The phage shock proteins (Psp) system is activated in bacteria in response to various membrane stress conditions. PspA, the main Psp effector, preserves the integrity and functions of the bacterial inner membrane. Here, we present the 3.6 Å resolution cryo-EM structure of PspA assembled in helical rods. The structure reveals that PspA adopts a canonical ESCRT-III fold in an extended open conformation with the C-terminal helix facing the outside of the helical tube. In addition to the structural homology, we vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 107 publications
5
12
0
Order By: Relevance
“…In this study, we use cryo-EM to show that Vipp1 and PspA form ESCRT-III-like filaments and provide a mechanism for Vipp1-mediated membrane remodeling. This is in line with parallel work carried out by other groups ( Gupta et al, 2021 ; Junglas et al, 2021 , this issue of Cell ). Collectively, our data show that the wider ESCRT-III family of polymers, which includes Vipp1 and PspA, arose prior to the divergence of bacteria and archaea over 3 billion years ago and play common, conserved roles in membrane remodeling and repair across all domains of life.…”
Section: Introductionsupporting
confidence: 90%
“…In this study, we use cryo-EM to show that Vipp1 and PspA form ESCRT-III-like filaments and provide a mechanism for Vipp1-mediated membrane remodeling. This is in line with parallel work carried out by other groups ( Gupta et al, 2021 ; Junglas et al, 2021 , this issue of Cell ). Collectively, our data show that the wider ESCRT-III family of polymers, which includes Vipp1 and PspA, arose prior to the divergence of bacteria and archaea over 3 billion years ago and play common, conserved roles in membrane remodeling and repair across all domains of life.…”
Section: Introductionsupporting
confidence: 90%
“…Indeed, such polymer flexibility would open the possibility of adapting to a wide range of diverse curvatures, including highly curved filaments, by the same polymer as well as accumulating elastic energy within the filaments (Figure 1C). In support of this, the recent structures of the plastid and bacterial homologs of ESCRT-III called Vipp1 (vesicle inducing protein in plastids 1, also named IM30) and PspA, respectively, show that many intermediates from semi-open to fully open conformations can polymerize in rings of different curvatures [17][18][19]. By contrast, the head-to-tail arrangement of the closed conformation displays much less intersubunit contacts and can be assumed to result in a more rigid filament, which is less resistant to torsional stress (Figure 1B).…”
Section: Open Accessmentioning
confidence: 89%
“…This one-fits-all ability of ESCRT-III can possibly be traced back to its ancient origin, before the split of archaea and eukaryotes, and hints toward its unique position as the sole means of membrane remodeling in these ancient organisms. The roots of ESCRT-III might even be predated to the last universal common ancestor (LUCA), as recent studies identified ESCRT-III homologs in bacteria, which act collectively in membrane repair at damage sites and in chloroplast membrane remodeling [17][18][19]. Ultimately, more functional and structural studies are needed to fully elucidate the molecular bases of ESCRT-III-mediated membrane remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, due to the basket-like structure of IM30 rings, the structure of IM30 monomers is somewhat distorted in the first three layers of a ring [22]. When natively folded SynPspA was compared to in vitro refolded SynPspA, formation of the prototypical rod structures was observed, but the refolded rods appeared to exhibit extended lengths and even looked more regular compared to the natively folded protein [21]. Due to these observations, we next tested whether the in vitro refolded IM30 rings still have a GTP/ATP-hydrolyzing activity.…”
Section: Im30 Nucleotide Binding Is Not Required For Im30 Ring Formationmentioning
confidence: 99%
“…PCC 73102) and PspA (Synechocystis sp. PCC 6803) have been made available [21][22][23]. PspA/ IM30 monomers are mainly a-helical when organized into high molecular mass oligomers, with flexible linkers connecting individual a-helical regions [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%